THE EFFECT OF PRICE DISCOUNT AND ELECTRONIC WORD OF MOUTH ON IMPULSE BUYING AT MARKETPLACE SHOPEE: Study on Students of Universitas Indonesia Membangun Bandung - Utami, Widyastuti Nurmalia; Juanda, Trysna Aditiya (Journal of Business and Management Inaba, 2022)
The purpose of this study was to determine the effect of Price Discount and Electronic Word of Mouth on Impulse Buying in the Shopee Marketplace. The research method used is a quantitative research method with a descriptive and verification approach. The type of data used is primary data and secondary data with data collection using questionnaires and search data through library research and online research. Sampling technique using Non-Probability Sampling with Purposive Sampling method with the number of respondents as many as 80 respondents. Prerequisite testing includes validity test, reliability test, descriptive analysis, verification analysis and hypothesis testing. The results showed that Price Discounts were in the sufficient category with a score of 1290 and Electronic Word of Mouth was classified in the sufficient category with a score of 1693. Price Discounts had a positive and significant effect on Impulse Purchases, this statement was evidenced by the value of tcount > ttable (2,441 > 1,991) and value Sig. namely 0.001 < 0.05, Electronic Word of Mouth has a positive and significant effect on Impulse Buying, this is evidenced by the value of tcount > ttable (3.017 > 1.991) and the value of Sig. ie 0.020 < 0.05. Price Discount and Electronic Word of Mouth have a simultaneous effect on Impulse Buying, based on the results of simultaneous hypothesis testing (F test), obtained Fcount > Ftable (7,994 > 3.12) and the value of Sig. 0.003 < 0.05.